Measurement of leak volume as a diagnostic predictor of post-extubation stridor in pediatric patients - Jetanachai, Pravit; Pojthaveekiet, Jariya (Indonesian Pediatric Society, 2024)
Background Endotracheal intubation can cause post-extubation stridor (PES). The PES may prolong the length of stay in the hospital and be associated with increased morbidity and mortality, particularly if re-intubation is necessary. The leak volume (LV) test is a simple method to detect airway edema. Objective To evaluate the efficacy of LV and percent leak volume (PLV) in predicting PES. Methods Inspired tidal volume (VTi) and expired tidal volume (VTe) were observed for six respiratory cycles during positive pressure ventilation before extubation. The average of the six VTi and six VTe values were recorded. The LV was the difference between average VTi and average VTe. The conversion of the ratio of LV to average VTi into percentage was defined as PLV. Both LV and PLV were analyzed to determine cut-off values in predicting PES. Results Among 77 patients, 39 patients (50.6%) developed PES. Both LV and PLV showed a significant decrease in patients with PES.The ROC analysis showed that LV at a cut-off point of < 18.34 ml gave a sensitivity of 82.1% and specificity of 57.9%, whereas PLV < 13.83% yielded 79.5% sensitivity and 57.9% specificity for predicting PES. The LV and PLV had an area under the ROC curve of 0.770 (95%CI 0.665 to 0.874; P<0.001) and 0.706 (95%CI 0.59 to 0.821; P=0.01) respectively. Conclusion Leak volume and percent leak volume can be used as markers to predict PES in pediatric patients.